Walking Exercise in Phase II Cardiac Rehabilitation to Improve Aerobic Capacity in Patients with Congestive Heart Failure due to Three-Vessel Coronary Artery Disease - Farah Rizki Amalia; Farid Rahman; Kadek Agustini Aryani (FORIKES, 2026)
Congestive heart failure (CHF) secondary to three‑vessel coronary artery disease (CAD 3VD) is characterized by high morbidity and markedly reduced functional capacity, highlighting the importance of effective and individualized rehabilitation strategies. Exercise‑based cardiac rehabilitation, particularly during Phase II, plays a critical role in restoring functional performance, improving cardiovascular efficiency, and enhancing quality of life in high‑risk cardiac patients. This study aimed to evaluate the safety and clinical effectiveness of a Phase II cardiac rehabilitation program incorporating structured walking exercises in a patient with CHF and CAD 3VD. A single‑case design was applied to a 54‑year‑old male diagnosed with CHF and CAD 3VD. The intervention consisted of ten supervised sessions of moderate‑intensity aerobic exercise using track and treadmill walking. Clinical outcomes were assessed using the Six‑Minute Walk Test (6MWT), metabolic equivalents (METs), heart rate–walking speed index (HRWSI), vital signs, and perceived exertion. Hemodynamic responses were monitored throughout all sessions to ensure safety and tolerance. Following completion of the program, the patient demonstrated clinically meaningful improvements in functional and aerobic capacity. The 6MWT distance increased from 428 to 535 meters, METs improved from 4.8 to 5.7, and HRWSI increased from 1.21 to 1.50. These gains were accompanied by stable hemodynamic parameters and reduced perceived exertion, indicating enhanced cardiovascular efficiency and improved exercise tolerance. In conclusion, supervised, progressive walking exercise within a Phase II cardiac rehabilitation program is safe, feasible, and effective for improving functional capacity in high‑risk patients with CHF and CAD 3VD. The observed improvements support the integration of structured walking modalities as a core component of individualized cardiac rehabilitation.Keywords: congestive heart failure; cardiac rehabilitation phase II; walking exercise; aerobic capacity; physiotherapy